DESIGN OF RE-DIRECTIVE CRASH-CUSHION BASED ON COLLISION SAFETY - LEI ZhengBao; CHEN XiaoYong; ZHANG JiaBo (Jixie qiangdu)
Aiming at the current situation that the energy absorbing unit of the re-directive crash-cushion squeezes the corrugated plates on both sides during the collision deformation,causing secondary damage caused by the wavy plate scattering,an "H"type energy absorbing unit configuration is proposed. According to Standard for Safety Performance Evaluation of Highway Barriers（ JTG B05-01-2013）,a TA grade re-directive crash-cushion is designed to meet the collision speed of 80 km/h requirement. Meanwhile,the finite element simulation model of vehicle and crash-cushion is established and combined with the collision simulation test,the collision safety of TA grade re-directive crash-cushion is comprehensively analyzed. It shows that the vehicle has no rollover,climbing or riding span. The maximum accelerations at each collision condition are 17. 3 g,16. 5 g,14. 6 g and 8. 1 g,which meet the requirement of the evaluation criteria for collision safety laws.